2017
DOI: 10.1038/s41467-017-01923-4
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal infection and contact transmission of Zika virus in guinea pigs

Abstract: Zika virus (ZIKV) is primarily transmitted to humans through mosquito bites or sexual contact. The excretion and persistence of contagious ZIKV in various body fluids have been well documented in ZIKV patients; however, the risk of direct contact exposure remains unclear. Here, we show that guinea pigs are susceptible to ZIKV infection via subcutaneous inoculation route; infected guinea pigs exhibit seroconversion and significant viral secretion in sera, saliva, and tears. Notably, ZIKV is efficiently transmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 51 publications
5
63
3
Order By: Relevance
“…However, the explosive growth of ZIKV research since 2015 has spurred the development of new animal models, revealing pathogenic mechanisms and providing systems for evaluating therapeutic interventions. The most significant models of ZIKV infection are non-human primates and mice (7), but ZIKV disease also has been studied in guinea pigs, hamsters, tree shrews, and swine (27-35). Mice offer significant advantages in terms of cost, scale, speed, and genetic tractability, enabling mechanistic studies that are not feasible in non-human primate models.…”
Section: Discussionmentioning
confidence: 99%
“…However, the explosive growth of ZIKV research since 2015 has spurred the development of new animal models, revealing pathogenic mechanisms and providing systems for evaluating therapeutic interventions. The most significant models of ZIKV infection are non-human primates and mice (7), but ZIKV disease also has been studied in guinea pigs, hamsters, tree shrews, and swine (27-35). Mice offer significant advantages in terms of cost, scale, speed, and genetic tractability, enabling mechanistic studies that are not feasible in non-human primate models.…”
Section: Discussionmentioning
confidence: 99%
“…Several other animal models have been used to study ZIKV but most are not focused on sexual transmission. These models include guinea pigs [109][110][111], hamsters [112], bats [113], chick embryos, piglets [114,115] and boars [116]. Porcine fetuses were shown to present mild to severe neuropathology upon ZIKV infection [114,115].…”
Section: Other Animal Modelsmentioning
confidence: 99%
“…One study with ZIKV challenge mid-gestation showed no evidence of infection [109]; however, Kumar et al show guinea pigs inoculated subcutaneously with PRVABC59 had viremia and presented signs such as fever, hunched posture and detectable viral RNA in the blood [110]. Deng et al showed that intranasally-infected guinea pigs have virus in the sera, saliva and tears [111].…”
Section: Other Animal Modelsmentioning
confidence: 99%
“…Guinea pigs have also been intranasally infected with ZIKA virus (ZIKAV). Nasal infection with ZIKAV results in infection of the brain, parotid glands, tears, saliva and sera but NALT immune responses were not evaluated (Deng et al, 2017). Of interest, nasal vaccination of guinea pigs with a genital herpesvirus HSV2 vaccine results in protection to genital herpes and elicits systemic specific IgG but not IgA titers (Persson et al, 2016).…”
Section: Rats and Guinea Pigs As Models Of Human Nasal Diseasesmentioning
confidence: 99%
“…After 7 days post inoculation, IgM and IgA antibodies were detected, followed by IgG. Thus, a strong infection in the nasal mucosa was established in A129 mice (Deng et al, 2017). A vaccine against the envelope protein E of ZIKAV was tested in this mouse strain and production of neutralizing antibodies was able to confer protection against ZIKAV and other Flaviviridae (Sumathy et al, 2017).…”
Section: Mouse Models Of Human Nasal Diseases: What Are the Limitations?mentioning
confidence: 99%